Who in hands is sus management? Perceptions of municipal managers on management - Santos, Ezilaine Albino Monteiro (2017)
This study had as goal to analyze the perceptions of the municipal health managers of a regional interagency committee of the State of Goiás, on the instruments of management of the Unified Health System (UHS). This is a descriptive study, with qualitative approach, developed in a health region and the sample was composed by nine managers. The study shows the female predominance in UHS management. Regarding the level of education, one note that 78% of the managers have higher education. The data showed that 100% of the managers said assume the position of the health municipal system management by means of political statement. Thus, the municipal management of the Unified Health System is often carried out by individuals, although most of them has higher education in health, with weak and inefficient knowledge regarding the design of UHS and basic management tools.